2018
DOI: 10.12659/msm.909550
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Passive Stiffness of Medial and Lateral Heads of Gastrocnemius Muscle, Achilles Tendon, and Plantar Fascia at Different Ankle and Knee Positions Using the MyotonPRO

Abstract: Background The aim of this study was to assess the passive stiffness of the medial and lateral gastrocnemius (MG and LG), Achilles tendon (AT), and plantar fascia (PF) at different ankle and knee positions. Material/Methods Stiffness was assessed using a portable hand-held device (MyotonPRO). In 30 healthy participants (15 males, 15 females) with the knee fully extended or flexed 90°, stiffness of the MG, LG, AT, and PF was measured at 50° plantar flexion, 0° (neutral p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
51
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(57 citation statements)
references
References 39 publications
5
51
1
Order By: Relevance
“…However, the same relationship did not hold when the knee was flexed to 90°. This result is consistent with that of Huang et al 28 , who used MyotonPRO for their assessment. Hirata et al 35 also found that the stiffness of the MG was higher than that of the LG at DF25°.…”
Section: Effects Of Ankle and Knee Angle On The Stiffness Of The Mgsupporting
confidence: 93%
See 2 more Smart Citations
“…However, the same relationship did not hold when the knee was flexed to 90°. This result is consistent with that of Huang et al 28 , who used MyotonPRO for their assessment. Hirata et al 35 also found that the stiffness of the MG was higher than that of the LG at DF25°.…”
Section: Effects Of Ankle and Knee Angle On The Stiffness Of The Mgsupporting
confidence: 93%
“…The SOL was measured in the distal half of the SOL for visualization of the distal SOL fascicles alone 27 . The PF was assessed at 3 successive levels: between the first and second metatarsal bone, on the anterior edge of the inferior calcaneal border and in the posterior section of the PF 8,28 . The length was measured with a tape measure, and a black pen was used to mark the location of the measurement site.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study supports these findings in both non-weight bearing and weight bearing positions. In addition to this our study utilised eight points of measurement at intervals of 2cm along the Achilles Tendon unlike Huang et al (32) who utilised three points of measurement at 0 cm (Achilles insertion at calcaneum), 3 cm and 6cm along the tendon.…”
Section: Discussionmentioning
confidence: 99%
“…It is likely that this demonstrates strain hardening under loading of the tissues with increase of logarithmic decrement during weight bearing (33). Previous studies utilising the MyotonPRO have evaluated tendon and muscle stiffness unloaded (13,15) and utilising minimal points of measurement (32). In order to simulate loading during posture, gait or other activities, the clinician may benefit from carrying out measurement and assessment of soft tissues when loaded and unloaded.…”
Section: Discussionmentioning
confidence: 99%